Patient-related risk factors for tooth loss in aggressive periodontitis after active periodontal therapy - Bäumer, Amelie; Sayed, Nihad el; Kim, Ti-Sun; Reitmeir, Peter; Eickholz, Peter; Pretzl, Bernadette (Journal of clinical periodontology, 2011)
Bäumer A, El Sayed N, Kim T-S, Reitmeir P, Eickholz P, Pretzl B. Patient-related risk factors for tooth loss in aggressive periodontitis after active periodontal therapy. J Clin Periodontol 2011; 38: 347-354. doi: 10.1111/j.1600-051X.2011.01698.x. Abstract Objectives: Evaluation of patient-related risk factors contributing to tooth loss and recurrence of periodontitis 10.5 years after initial therapy in patients with aggressive periodontitis (AgP). Material and Methods: Eighty-four of 174 patients were included. Re-examination consisted of patient's history, clinical examination and test for interleukin (IL)-1 composite genotype. Patients' charts were searched for regularity of maintenance and initial diagnosis. Statistical analysis was performed using Poisson and logistical regression analysis. Results: The responder rate was 48%. Thirteen of 84 patients presented a localized AgP, 68 were females and 29 smoked. One hundred and thirteen teeth out of 2154 were lost after therapy (1.34 teeth/patient). Age (p=0.0018), absence of IL-1 composite genotype (p=0.0091) and educational status (p=0.0085) were identified as statistically significant risk factors for tooth loss. Twenty patients exhibited recurrence of periodontitis at re-examination. Smoking (p=0.0034) and mean Gingival Bleeding Index (GBI) (p=0.0239) contributed significantly to recurrence of disease. No patient participating regularly in supportive periodontal therapy (SPT) showed disease recurrence. Conclusion: Age, absence of IL-1 composite genotype and low social status are detected as risk factors for tooth loss. Smoking and high mean GBI are associated with an increased risk for recurrence of periodontitis, whereas regular SPT acts as a protective factor.